Self-assembly and β-carotene loading capacity of hydroxyethyl cellulose-graft-linoleic acid nanomicelles. (10th July 2016) - Yang, Yang; Guo, Yanzhu; Sun, Runcang; Wang, Xiaohui
Highlights: A new amphiphilic cellulose derivative (HEC-g-LA) was prepared. HEC-g-LA can form stable nanomicelles in water. HEC-g-LA micelles have good encapsulation efficiency and drug loading ability for β-carotene. β-carotene loaded HEC-g-LA micelle showed a sustained release behavior in PBS medium. Those nanomicelles are potential nanocarriers of hydrophobic active compounds for functional food applications. Abstract: A series of linoleic acid conjugated hydroxyethyl cellulose polymers (HEC- g -LA) were synthesized and characterized. And their solubilities in a variety of solvents were compared. The prepared HEC- g -LA polymers showed typical properties of amphiphilic polymers and were able to self-assemble into spherical nanomicelles in aqueous solution. The micelle sizes and critical micelle concentrations (CMC) were found correlated with the molecular structure of polymers, and were varied in the range of 20–50 nm and 1.92–21.76 μg/ml, respectively. Furthermore, the hydrophobic active component β-carotene (β-C) was successfully encapsulated into the HEC- g -LA micelles by sonication-dialysis method. The β-C encapsulation efficiency and loading content were found to be as high as 84.67% (w/w) and 4.23%. The results of in vitro release showed that the encapsulated β-C was continuously released from the micelles in phosphate buffered saline (PBS) medium for about 7 days. The self-assembled HEC- g -LA nanomicelles are potential nanocarriers of hydrophobic active compounds for functional food applications.